Gamblang (Steel and Brilliant Mental Generation) as an Effort to Improve Mental Health of School-Based Adolescents at SMK Negeri III Tahuna - Tooy, Gracia Christy; Bajak, Chatrina Maria Agustina; Umboh, Melanthon Junaedi; Patras, Mareike Doherty; Tatangindatu, Maryati Agustina; Wuaten, Grace Angel (Civiliza Publishing, 2025)
The Sangihe Islands Regency is an outermost Indonesian archipelago with a significant number of adolescents and faces serious challenges related to adolescent mental health. One prominent case was a suicide attempt by a student at SMK Negeri 3 Tahuna due to depression, reflecting the importance of psychosocial interventions in the school environment. The